2018 IEEE Power &Amp; Energy Society General Meeting (PESGM) 2018
DOI: 10.1109/pesgm.2018.8586370
|View full text |Cite
|
Sign up to set email alerts
|

Participation of an Energy Storage Aggregator in Electricity Markets

Abstract: An important function of aggregators is to enable the participation of small energy storage units in electricity markets. This paper studies two generally overlooked aspects related to aggregators of energy storage: i) the relationship between the aggregator and its constituent storage units and ii) the aggregator's effect on system welfare.Regarding i), we show that short-term outcomes can be Pareto-inefficient: all players could be better-off. In practice, however, aggregators and storage units are likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…The provision of the ASs caused deviation from the reference operation points of aggregated resources, hence, the values of the objective function for all scenarios were lower compared to the reference case. The difference between the obtained value of the objective function (for Scenarios [1][2][3][4][5][6] and reference value should be treated as the minimum price of the offer for AS provision (Figure 11). The lowest profits were obtained in Scenarios 2, 4 and 6 in which RES curtailment was allowed, and a significant decrease in incomes due to lost generation occurred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The provision of the ASs caused deviation from the reference operation points of aggregated resources, hence, the values of the objective function for all scenarios were lower compared to the reference case. The difference between the obtained value of the objective function (for Scenarios [1][2][3][4][5][6] and reference value should be treated as the minimum price of the offer for AS provision (Figure 11). The lowest profits were obtained in Scenarios 2, 4 and 6 in which RES curtailment was allowed, and a significant decrease in incomes due to lost generation occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Small ESSs for household application, due to their growing number, can be aggregated The small size of distributed assets is a problem causing a lack of ability to participate in wholesale markets such as balancing markets and AS markets; moreover, legal obligations constitute a barrier for some entities. Therefore, an additional agent, that is, an aggregator, is required [1][2][3][4]. Figure 1 depicts the DRA coordinator as an entity responsible for distributed asset coordination and control enabling active participation of DERs in the management of power system operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies identified the role of aggregators for ES in providing different services in the energy markets. However, the business case for aggregators is seen as hampered by the regulatory frameworks that prevent wider market access [41,101,102]. In 2016, the EC required member states to facilitate direct market access to the retail market [103].…”
Section: Ancillary Services Aggregationmentioning
confidence: 99%
“…Applying VCG auction to the electricity market has been demonstrated to improve the economic benefits of EPs [12]. Moreover, VCG auction has also been demonstrated to be applicable to the storage of energy, such as for ensuring the truthful declaration of battery energy storage parameters [13].…”
Section: Introductionmentioning
confidence: 99%